Anti fuzzy sub KS-semigroups - Platil, Longrio C.; Vilela, Jocelyn P. (2015)
A BCK-algebraic structure of a set X with one binary operation and a KS-semigroup is an algebraic structure with two binary operations which is a BCK-algebra with respect to the first binary operation and a semigroup with respect to the second bianry operation satisfying left and right distributive laws. In this paper, we introduce the notion of anti fuzzy KS-semigroup and investigate some of their related properties. The purpose of this study is to anti fuzzify KS-semigroups.
Keywords: Algebra